Clinical and genetic characteristics of Charcot–Marie–Tooth disease type 4D (type Lom) in Russia - A. F. Murtazina; O. A. Shchagina; T. B. Milovidova; E. L. Dadali; G. E. Rudenskaya; S. A. Kurbatov; T. V. Fedotova; S. S. Nikitin; P. A. Sparber; M. D. Orlova; A. V. Polyakov (Нервно-мышечные болезни, 2020)
Introduction. Charcot–Marie–Tooth disease type 4D is a hereditary demyelinating neuropathy, that occurs with the high frequency in patients of Roma origin. It is characterized by early onset at the age of 2–10 years and hearing impairment, manifested by the 3rd decade of life.Aim of the study. To describe the clinical and genetic characteristics of Charcot–Marie–Tooth disease type 4D in Russian patients of Roma origin.Materials and methods. For 14 probands from unrelated families of Roma origin with a clinical diagnosis of Charcot–Marie–Tooth disease, genetic tests for the pathogenic variants c. 442C>T in the NDRG1 gene and c. 3325C>T in the SH3TC2 gene was carried out. For 8 patients with Charcot–Marie–Tooth disease type 4D, detailed clinical and electrophysiological examination was performed.Results. In 11 families of Roma origin, the c. 442C>T pathogenic variant in the NDRG1 gene in a homozygous state was detected, which accounted for 79 % all observed Roma patients with Charcot–Marie–Tooth disease. There are 12 of the 14 tested families live in the European part of Russia, 7 of them are from nearby regions. The average age of onset was 3.3 years. The first symptom in 7 of 8 patients was gait disturbances. At the time of examination (age range 6–19 years), all patients showed marked hypotrophy and weakness of the feet, lower leg, hands muscles, feet deformities, reduction or loss of tendon reflexes.Discussion. Due to the detection of only one pathogenic variant in most Russian patients of Roma origin with Charcot–Marie–Tooth disease, the knowledge of the ethnicity of a proband with early myelinopathy can significantly simplify the confirmation of the diagnosis on the molecular level.